(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Foreign Direct Investment (FDI) is critical for the growth of a country. Domestically available capital may not always be sufficient for a country’s long-term development. Foreign investment is seen as a way to bridge the savings and investment gaps that exist domestically. Foreign Direct Investment (FDI) has become a major source of foreign capital flow and a leading source of external finance for developing economies like India. India is capable of attracting much larger FDI investments. Emerging economies around the world have seen a massive increase of foreign direct investment (FDI) since the start of globalization in the last two decades. Despite India’s relatively late entry into the FDI scene compared to other East Asian nations, the country’s large market potential and a relatively open policy environment have kept it a popular choice for foreign investors. An important method widely used in developing countries to increase capital formation, create jobs, and thus facilitate growth and development is attracting foreign investment. Foreign direct investment (FDI) is widely regarded as a key resource for developing countries’ economic growth